Serum biomarkers combined with ultrasonography for early diagnosis of non-alcoholic fatty liver disease conﬁrmed by magnetic resonance spectroscopy - Qian Ling-ling; Wu Liang; Zhang Lei; Zhang Jing; Zhou Jia; Li Yue-hua; Fang Qi-chen; Li Hua-ting; Jia Wei-ping (Acta Pharmacologica Sinica, 2020)
Magnetic resonance spectroscopy (MRS) is notably accurate for even minimal degree of hepatic steatosis in non-alcoholic fatty liver disease (NAFLD). But routine use of MRS is limited by its cost and availability. In this study, we developed a diagnostic model combining ultrasonography with biomarkers to identify mild NAFLD, with MRS as the reference standard. A total of 422 eligible subjects were enrolled. The serum levels of ﬁbroblast growth factor 21 (FGF21), cytokeratin 18 M65ED, proteinase 3, neutrophil elastase, alpha-1 antitrypsin, and neutrophil elastase/alpha-1 antitrypsin were measured using ELISA assays. We found that among the six biomarkers, only serum FGF21 was independently associated with intrahepatic triglyceride content (IHTC, standardized β = 0.185, P< 0.001) and was an independent risk factor for mild NAFLD. Thus, we established a Mild NAFLD Model based on FGF21, alanine transaminase, triglycerides, and body mass index. The area under the receiver-operating characteristic curve of the Mild NAFLD Model was 0.853 (95% conﬁdence interval: 0.816–0.886). Furthermore, a two-step approach combining ultrasonography with the Mild NAFLD Model displayed a better sensitivity for diagnosing mild NAFLD compared with each method alone, with a sensitivity of 97.32% and a negative predictive value of 85.48%. This two-step approach combining ultrasonography and the Mild NAFLD Model derived from serum FGF21 improves the diagnosis of mild NAFLD and can be applied to the early diagnosis of NAFLD in clinical practice.